Higher education research monograph series:Industrial training practices in Malaysian undergraduate engineering programme. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2006)

(untitled)
The primary objective of this project is to explore approaches to enhance the effectiveness of industrial training conducted by institutions of higher education in Malaysia. Industrial training is viewed as an important strategy to expose students to real work life and to equip them with the necessary skills so that they would be job ready when they graduate.